The Effect of Organizational Cultures on Relationships between IT Governance and Individual Behavior - Pedro Fernandes; Rúben Pereira; Guilherme Wiedenhöft (Ital Publication, 2023)
Background: Organizations allocate substantial resources to Information Technology (IT) to ensure its long-term success. Hence, effective IT Governance (ITG) is crucial for business/IT alignment. However, factors like employee behavior and Organizational Culture (OC) play vital roles in applying ITG but remain underexplored. Objectives: This study aims to bridge this gap by examining the relationship between ITG and Organizational Citizenship Behavior (OCB). Additionally, it investigates the moderating effect of different cultures in the Organizational Culture Assessment Instrument (OCAI) on the ITG-OCB relationship. Methods/Analysis: A survey was conducted involving 513 employees from over 150 companies worldwide. The data were analyzed using partial least-squares structural equation modeling (PLS-SEM). Findings: This study confirms that institutionalizing ITG enhances OCB. Furthermore, a moderating effect was observed in most relationships, highlighting the influence of different OC types. Market and hierarchy cultures exhibited the most significant moderating effect. Novelty: This research contributes to the understanding of ITG's impact on employee behavior, extending the investigation to new dimensions of OCB and confirming the moderating role of OC. The practical implications of this study enable organizations to foster a culture that promotes ITG and cultivates employees' OCB, leading to improved business-IT alignment, enhanced IT-enabled value, and, ultimately, enhanced organizational effectiveness. Doi: 10.28991/ESJ-2023-07-05-010 Full Text: PDF